2023
DOI: 10.7717/peerj.14767
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a ceRNA network of regulated ferroptosis in doxorubicin-induced myocardial injury

Abstract: Background Ferroptosis and long-noncoding RNAs (lncRNAs) play crucial roles in doxorubicin (DOX)-induced myocardial injury (DIMI). Nevertheless, there is no research to construct competing endogenous RNAs (ceRNAs) network between lncRNAs and ferroptosis-related key gene. So our research was designed to screen ferroptosis-related genes from differentially expressed mRNAs in DIMI and construct lncRNAs regulated ferroptosis-related key gene ceRNAs network. Methods The male mice were injected with DOX intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In recent years, much attention has been paid to studying the role of non-coding RNAs (ncRNAs), particularly microRNAs, long non-coding RNAs (lncRNAs), and circular RNAs in the pathogenesis of cardiovascular diseases, in particular, in the regulation of ferroptosis [60,61].…”
Section: The Role Of Non-coding Rna In the Regulation Of Ferroptosis ...mentioning
confidence: 99%
“…In recent years, much attention has been paid to studying the role of non-coding RNAs (ncRNAs), particularly microRNAs, long non-coding RNAs (lncRNAs), and circular RNAs in the pathogenesis of cardiovascular diseases, in particular, in the regulation of ferroptosis [60,61].…”
Section: The Role Of Non-coding Rna In the Regulation Of Ferroptosis ...mentioning
confidence: 99%
“…A growing number of evidence suggests that long non-coding RNA (lncRNA) could repress target mRNAs through miRNA response elements of a lncRNA-associated competing endogenous RNA (ceRNA) network and serve as a crucial regulatory mechanism in HCM such as cardiac hypertrophy-related factor (CHRF), ROR, H19, Plscr4, MEG3 and CYTOR [8]. Meanwhile, a large number of studies have shown that lncRNAassociated ceRNA regulatory networks also play an important role in ferroptosis [9][10][11][12], suggesting a possible regulatory role for ferroptosis-related ceRNA regulatory networks in hypertrophic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of evidence suggests that long non-coding RNA (lncRNA) may repress target mRNAs through miRNA response elements of an lncRNA-associated competing endogenous RNA (ceRNA) network and serve as a critical regulatory mechanism in HCM such as cardiac hypertrophy-related factor (CHRF), ROR, H19, Plscr4, MEG3 and CYTOR [8]. Numerous studies indicate that lncRNA-associated ceRNA regulatory networks have an essential function in ferroptosis [9][10][11][12], suggesting a potential regulatory role for ferroptosis-related ceRNA regulatory networks in hypertrophic cardiomyopathy.…”
mentioning
confidence: 99%